(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2018)
The purpose of this study is to invite the reader to revisit the case law of the Superior Court of Justice to see if it is possible to draw the conclusion that the institute of spontaneous denunciation is inapplicable to cases of non-compliance with instrumental duties; and, if this is the position adopted until then, if it is the one that best reflects the law in place. The author also suggests that the institute of spontaneous denunciation fully adheres to cases in which there is non-compliance with instrumental duties, either due to the nature of the institute, the normative wording of article 138 of the National Tax Code, or even as a result of the principle of equality.